Influence of Trans Fat on Skin Damage in First‐Generation Rats Exposed to UV Radiation. (20th January 2015) - Barcelos, Raquel Cristine S.; Vey, Luciana T.; Segat, Hecson Jesser; Benvegnú, Dalila M.; Trevizol, Fabíola; Roversi, Karine; Roversi, Katiane; Dias, Verônica T.; Dolci, Geisa S.; Kuhn, Fábio T.; Piccolo, Jaqueline; CristinaVeit, Juliana; et al.
Abstract The influence of trans fatty acids (TFA) on lipid profile, oxidative damage and mitochondrial function in the skin of rats exposed to ultraviolet radiation (UVR) was assessed. The first‐generation offspring of female Wistar rats supplemented from pregnancy with either soybean oil (C‐SO, rich in n–6 FA; control group) or hydrogenated vegetable fat (HVF, rich in TFA) were continued with the same supplements until adulthood, when half of each group was exposed to UVR for 12 weeks. The HVF group showed higher TFA cutaneous incorporation, increased protein carbonyl (PC) levels, decreased functionality of mitochondrial enzymes and antioxidant defenses of the skin. After UVR, the HVF group showed increased skin thickness and reactive species (RS) generation, with decreased skin antioxidant defenses. RS generation was positively correlated with skin thickness, wrinkles and PC levels. Once incorporated to skin, TFA make it more susceptible to developing UVR‐induced disorders.